Implementasi Model Ontologi dalam Representasi Pengetahuan Anjing Ras Menggunakan Metode Methontology - Anak Agung Gede Angga Putra Wibawa; I Ketut Gede Suhartana (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
One of the animals closest to humans is a dog. This animal is widely kept because it is one of the smartest animals and can function as a stress reliever and provide comfort for its owner. Dog breeds are very diverse, with each breed having different characteristics. The large population of dog breeds sometimes makes people confused in choosing the right breed according to their personality and needs. Therefore, this study aims to build a knowledge structure that provides structured information about purebred dog breeds. Ontology is used as an approach to designing knowledge structures. This study focuses on the implementation of ontology using methontology that can describe each design stage in detail. The results of the study include 10 classes, 16 object properties, 8 data properties, and 105 individuals using protégé. Testing was carried out using OntoQA to measure quality and SPARQL Query to measure the accuracy of the answers. The results showed that the ontology model had good quality and was able to provide correct answers to the questions being tested.